Reflection of Religious Value in The Poem of Prayist - Abdul Asis (Balai Penelitian dan Pengembangan Agama Makassar, 2010)
In Buginese society Elong ugi means song. In literature, elong ugi is a kind of poetry that has similarity to poem andtraditional poetry. Elong ugi is an effective medium to express feeling and thought. Elong ugi to panrita is divided intoelong onronna sempqjannge andpangaja panrita sulesanae. The research used descriptive qualitative method involvingcollecting and analyzing data. Research found some reflections of religious value in elong ugi, which were I)virtue of praying, 2) the virtue ofgood behavior, 3) keeping clean, 4) self controlling, 5) daily worshipping, 6) doingmore prayers, and 7) having firmer belief and piety